2007
DOI: 10.4049/jimmunol.179.2.1138
|View full text |Cite
|
Sign up to set email alerts
|

NKT Cells Are Critical to Initiate an Inflammatory Response after Pseudomonas aeruginosa Ocular Infection in Susceptible Mice

Abstract: CD4+ T cells produce IFN-γ contributing to corneal perforation in C57BL/6 (B6) mice after Pseudomonas aeruginosa infection. To determine the role of NK and NKT cells, infected corneas of B6 mice were dual immunolabeled. Initially, more NKT than NK cells were detected, but as disease progressed, NK cells increased, while NKT cells decreased. Therefore, B6 mice were depleted of NK/NKT cells with anti-asialo GM1 or anti-NK1.1 Ab. Either treatment accelerated time to perforation, increased bacterial load and polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
(42 reference statements)
1
23
0
Order By: Relevance
“…These observations are consistent with an earlier study showing that depletion of NK and NK-T cells in P. aeruginosa results in decreased IFN-␥ RNA expression, impaired bacterial killing, and accelerated corneal perforation (34).…”
Section: Discussionsupporting
confidence: 93%
“…These observations are consistent with an earlier study showing that depletion of NK and NK-T cells in P. aeruginosa results in decreased IFN-␥ RNA expression, impaired bacterial killing, and accelerated corneal perforation (34).…”
Section: Discussionsupporting
confidence: 93%
“…It is thought that MD-2 expression is enabled by the infiltration of immune cells such as natural killer cells, which activate the JAK2/STAT1 transcription pathway and produce IFN-γ. 84,85 In a murine model of corneal inflammation, Chinnery et al 83 demonstrated that TLR4 activation on resident corneal macrophages and DCs stimulated macrophage and neutrophil recruitment and induced corneal haze.…”
Section: Pattern Recognition Mechanisms Activated By Microbial Pathogmentioning
confidence: 99%
“…However, the cellular and molecular mechanisms by which CFA activates NK cells and prevents disease remains unknown. NK cell activation has been shown to be dependent on NKT cells and, at least in part, their release of IFN-g after aGC treatment or microbial infection (20,32,55). However, NKT cells are not required for NK cells to function, as steady-state levels of NK cell cytotoxicity are similar between NKT cell-deficient (CD1d 2/2 or Ja281 2/2 ) and wild-type mice (32).…”
Section: Discussionmentioning
confidence: 87%